1998
DOI: 10.1681/asn.v9101915
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of renal outcome in anti-myeloperoxidase-associated necrotizing crescentic glomerulonephritis.

Abstract: Patients with anti-myeloperoxidase (MPO)-associated necrotizing crescentic glomerulonephritis (NCGN) may develop chronic renal failure (CRF) leading to end-stage renal disease despite an initially favorable response to treatment. The aim of this study was to determine the prognostic value of clinical, laboratory, and histopathologic features at the time of presentation and during follow-up for the development of CRF in 21 consecutive anti-MPO-positive patients with NCGN. Renal function did not recover in two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…24,27,28 Although the level of proteinuria at diagnosis has been associated with the presence of chronic glomerular lesions and unfavorable kidney outcome in unadjusted analyses, 29,30 little is known about the significance of persistent proteinuria at the end of induction therapy in AAV, in contrast to data observed in other glomerular diseases 16,17,31 as well as in cohorts with CKD. 14 Although patients with poor kidney outcome displayed higher proteinuria during follow-up in a small analysis of 21 patients with MPO-ANCA, 32 ANCA, anti-neutrophil cytoplasmic autoantibody; CI, confidence interval; MPO, myeloperoxidase; PR3, proteinase 3; RTX, rituximab; sCreat, serum creatinine; sHR, subdistribution hazard ratio; UPCR, urine protein-creatinine ratio. sHRs were obtained using Fine and Gray competing risk regression after adjustment for each of the variables presented in this table.…”
Section: Discussionmentioning
confidence: 99%
“…24,27,28 Although the level of proteinuria at diagnosis has been associated with the presence of chronic glomerular lesions and unfavorable kidney outcome in unadjusted analyses, 29,30 little is known about the significance of persistent proteinuria at the end of induction therapy in AAV, in contrast to data observed in other glomerular diseases 16,17,31 as well as in cohorts with CKD. 14 Although patients with poor kidney outcome displayed higher proteinuria during follow-up in a small analysis of 21 patients with MPO-ANCA, 32 ANCA, anti-neutrophil cytoplasmic autoantibody; CI, confidence interval; MPO, myeloperoxidase; PR3, proteinase 3; RTX, rituximab; sCreat, serum creatinine; sHR, subdistribution hazard ratio; UPCR, urine protein-creatinine ratio. sHRs were obtained using Fine and Gray competing risk regression after adjustment for each of the variables presented in this table.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, the severity of proteinuria is associated with worse renal outcome, irrespective of baseline eGFR, [ 44 ] and is a strong predictor of ESKD [ 45 ]. In AAV, the degree of proteinuria might vary on a larger scale [ 46 ], but observational studies have found a positive correlation between baseline proteinuria and renal outcome [ 47 , 48 ]. On the other hand, de Joode et al .…”
Section: Which Kidney Surrogate Markers Are Used To Assess Renal Resp...mentioning
confidence: 99%